Pengaruh Strategi Pembelajaran Berorientasi Aktivitas Siswa Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa - Mu'arifah, Ulil; Hakim, Muhammad Luqman Hakim (Universitas Sarjanawiyata Tamansiswa, 2021)
. The purpose of this study was to determine the influence of student activity-oriented learning strategies on critical thinking skills and student learning outcomes of class XI MAN 2 Blitar. This study uses a quantitative approach with a quasi-experimental research design. Data collection using test and questionnaire methods. The test method is to obtain data on student learning outcomes while the questionnaire is to obtain data on students' critical thinking skills during the learning process based on indicators of critical thinking. The results of this study indicate that the application of student activity-oriented learning strategies affects students' critical thinking skills, which is indicated by the results of the t-test sample which is not homogeneous, namely the significance number = 0.000 / 2 = 0 <0.05. 2) Student activity-oriented learning strategies (PBAS) have an effect on student learning outcomes, this is evidenced by the learning outcomes of post-test answers obtained by the experimental class which are higher than the control class. This is indicated by the results of the free sample t-test, namely significance = 0.000 / 2 = 0 <0.05. 3) The ability to think critically in students has a linear or unidirectional relationship with learning outcomes. This is evidenced by the results of simple regression analysis, namely the linear regression equation shows significance = 0.011 <0.05 or has a positive relationship